Review of the global distribution and hosts of the fish parasitic isopod genus Renocila Miers, 1880 (Crustacea: Cymothoidae) with the description of a new species from Andaman Islands, India. Issue 43 (17th November 2021) - Aneesh, Panakkool Thamban; Nashad, Musaliyarakam; Bijukumar, Appukuttannair; Bineesh, Kinattumkara; Mohamed Hatha, Abdulla A.
ABSTRACT: The global distribution and host records of the external fish parasitic isopod genus Renocila Miers, 1880, are reviewed. A revised generic diagnosis is provided and 11 species of Renocila are regarded as Renocila incertae sedis . Renocila trillesi Aneesh and Kumar sp. nov., parasitizing the coral grouper, Cephalopholis miniata (Forsskål, 1775) collected off Junglighat, South Andaman, India, is described and illustrated, the second species of Renocila from the Indian EEZ. Renocila currently includes 20 valid species including Renocila trillesi Aneesh and Kumar sp. nov. Renocila trillesi Aneesh and Kumar sp. nov., is characterized by: anteriorly truncate rostrum with a ventral posteriorly directed anterior margin; antenna subequal to antennula; pereonite 7 posterolateral angle acute, pleon is 0.85 width of pereon; pleotelson broadly truncate, with weak median longitudinal carina; pereopods 1–3 each with a produced process on the posterodistal angle of basis, gradually increasing the length from 1–3; and pereopods 1–3 inferior margins of articles all without a process or lobe, though ischium of pereopods 1–7 carinate. The present paper also records Acanthurus mata (Cuvier, 1829) as a new host fish for recently described Renocila bijui Aneesh and Bruce 2020. A revised key to the global species is provided. http://www.zoobank.org/urn:lsid:zoobank.org:pub:A93A1180-8F8E-4023-BD9B-B64C102AC6B7